2016
DOI: 10.3390/rs8010042
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Soil Moisture Content and Soil Salt Concentration from Hyperspectral Laboratory and Field Data

Abstract: This research examines the simultaneous retrieval of surface soil moisture and salt concentrations using hyperspectral reflectance data in an arid environment. We conducted laboratory and outdoor field experiments in which we examined three key soil variables: soil moisture, salt and texture (silty loam, clay and silty clay). The soil moisture content models for multiple textures (M_SMC models) were based on selected hyperspectral reflectance data located around 1460, 1900 and 2010 nm and resulted in R 2 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…This means that when the moisture content increases, the spectral reflectance decreases. Researches also showed that the soil reflectance decreases with soil salt content [35,36]. In the current study, we took dried soil samples as the study object, which can be considered to have the same moisture content, and the main factors that determine the spectral reflectance are salt content and surface roughness.…”
Section: Discussionmentioning
confidence: 95%
“…This means that when the moisture content increases, the spectral reflectance decreases. Researches also showed that the soil reflectance decreases with soil salt content [35,36]. In the current study, we took dried soil samples as the study object, which can be considered to have the same moisture content, and the main factors that determine the spectral reflectance are salt content and surface roughness.…”
Section: Discussionmentioning
confidence: 95%
“…When salt efflorescence is partial, especially at coarse resolution, different soil type (e.g., texture, color) and roughness, presence of sparse vegetation, and surface water content can have confounding effects on salinity estimations. However, these effects can be accounted for, as presented by Xu et al (2016).…”
Section: Surface Soil Salinitymentioning
confidence: 99%
“…In the aforementioned studies, the laboratory measurements were collected using carefully prepared or dilute soil specimens under controlled conditions. Fewer studies were conducted under field conditions [23,25,26]. Among the numerous developed soil reflectance correlations in the literature, other soil parameters of interest have included clay content [9,14,24,[27][28][29][30], grain size [9,28,29,31], soil plasticity [24,32,33] and matric potential [24].…”
Section: Introductionmentioning
confidence: 99%